Leadership in Culturally Diverse Schools: The Administrative Practices of Canadian System Education Leaders Most Impactful in Student Global Competence Development - Nippard, Roger; Charoenarpornwattana, Paratchanun; Chuchuen, Rapin (Journal of Social Sciences and Humanities Research in Asia, 2022)
This paper reports on the qualitative portion of a mixed methods study examining the Leadership Quality Standard and administrative practices of thirteen (13) Alberta (Canada) System Education Leaders in two school systems. In both systems classroom cultural homogeneity had been intentionally disrupted through immigration, and the establishment of a robust international student program, and preparing slobally competent students was established as a strategic priority. The semi-structured interviews and document analysis highlighted the importance of globally contextualizing. This paper was conducted online by Zoom to interview the participants and document review. Data analysis using the constant comparative technique. The professional practice of school system leaders in their legislated professional leadership quality standards, and five administrative practice categories emerged as being strongly associated with the implementation of student global competence programming. These categories included a focus on equity, diversity, and inclusion; visionary leadership; pedagogical leadership; globalization of the curriculum; and global connections, relationships, and partnerships. The study findings extend the research base, particularly in the earlier formative years of primary and secondary education. With global competence joining literacy, numeracy, and science as a Programme for International Student Assessment foundational competency the findings are timely, providing a potential road map for those tasked with developing more globally competent students, schools, and school systems.